2018
DOI: 10.1002/jssc.201701234
|View full text |Cite
|
Sign up to set email alerts
|

Photografted methacrylate‐based monolithic columns coated with cellulose tris(3,5‐dimethylphenylcarbamate) for chiral separation in CEC

Abstract: A chiral capillary monolithic column for enantiomer separation in capillary electrochromatography was prepared by coating cellulose tris(3,5-dimethylphenylcarbamate) on porous glycidyl methacrylate-co-ethylene dimethacrylate monolith in capillary format grafted with chains of [2(methacryloyloxy)ethyl] trimethylammonium chloride. The surface modification of the monolith by the photografting of [2(methacryloyloxy)ethyl] trimethylammonium chloride monomer as well as the coating conditions of cellulose tris(3,5-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Methacrylate-based monolithic columns are one of the materials most prone to development. In addition to being practical, it is shown that the column can be applied sometimes without requiring any silanization pro-cess [105,106,[321][322][323] Denizli et al synthesized chiral monolithic capillary column based on butyl methacrylate in their studies in which the enantiomeric separations of including some of hydrophobic amino acids investigated, which N-Metacryloyl-L-Histidine monomer (MAH) and N-Metacryloyl-L-Glutamic Acid (MAGA) was used as chiral selectors, resptectively in CEC [324,325].…”
Section: Monolithsmentioning
confidence: 99%
“…Methacrylate-based monolithic columns are one of the materials most prone to development. In addition to being practical, it is shown that the column can be applied sometimes without requiring any silanization pro-cess [105,106,[321][322][323] Denizli et al synthesized chiral monolithic capillary column based on butyl methacrylate in their studies in which the enantiomeric separations of including some of hydrophobic amino acids investigated, which N-Metacryloyl-L-Histidine monomer (MAH) and N-Metacryloyl-L-Glutamic Acid (MAGA) was used as chiral selectors, resptectively in CEC [324,325].…”
Section: Monolithsmentioning
confidence: 99%
“…The most commonly used preparation method of polymer stationary phase with the desired surface chemistry was carried out via a one‐step molding process of direct in situ copolymerization of the functional monomer, crosslinker, initiator, and in the presence of an appropriate porogen . Concentration and composition of organic monomers are the main factors that affect the characters of monolithic column .…”
Section: Monolithic Capillary Electrochromatographymentioning
confidence: 99%
“…Usually, one-step chiral in-situ polymerization is employed to prepare chiral MCCs. The commonly used chiral stationary phases in MCCs are various derivatives of β-cyclodextrin [25][26][27][28], and others include cellulose [29][30][31], pepsin [32,33], polymyxin-B [34] and (S)-(-)−1-(2-naphthyl)ethylamine [35]. It is worth mentioning that metal-organic frameworks [29,32], COFs [30], and gold nanoparticles [36] can improve the enantioseparation ability of chiral MCCs.…”
Section: Introductionmentioning
confidence: 99%